Estudio de prefactibilidad para la instalación de un instituto de chino mandarín en Lima Metropolitana orientado al NSE A y B - Soto Torres, Diana Carolina (2022)
This prefeasibility study evaluates the implementation of a company that produces eco-friendly hair care products, specifically the production of shampoo-conditioner bars. To carry out the research, the scientific method was used, using primary and secondary sources to collect information. The main problem that the project seeks to address is the great pollution generated by the massive consumption of plastic in single-use products, which translates into millions of tons of waste after use. This problem is the basis of the research and the technical, economic, and social justification of the project. In addition, the context, objectives, hypotheses, and the respective conceptual and referential frameworks were determined. The market study determined a demand for 100 241 shampoo-conditioner bars, considering as potential customers people from NSE A and B of Metropolitan Lima. The analysis of the location of the plant determined that the plant will be in the district of Surquillo in Metropolitan Lima. The plant will occupy a surface area of 353 m², including the administrative area, and its plant capacity will be 123 552 bars. The technology chosen for the plant's production process consists of mixing, heating, molding, and cooling activities. The company has three areas, operations, commercial and administration and finance, which are made up of 18 employees, including a general manager. The investment required to carry out the project is S /. 1 309 178,64. Of the financial flow, a NPV of S /. 735 675,58, a B / C ratio of 1,937, an IRR of 43,05%, a payback period of 3,67 years at a cost of capital of 17.56%, a AER of 12%, with the shareholder contribution equivalent to 60% of the total investment. In addition, a social evaluation of the project was carried out, with which it was determined that the project has a positive impact on society.